DEVELOPMENT OF BIOLOGY LEARNING TOOLS USING DISCOVERY LEARNING ASSISTED BY PODCAST AND GOOGLE CLASSROOM TO IMPROVE SCIENTIFIC SKILLS AND COGNITIVE LEARNING OUTCOMES OF SENIOR HIGH SCHOOL STUDENTS - Elistika Oktaviyani; Ibrohim Ibrohim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
This research aims to produce biology learning tools using discovery learning-based online a valid, practical, and effective to improve the scientific skills and cognitive learning outcomes of students class X MIPA E2 Sma Negeri 5 Malang. The method of this research is research and development (R&D) with ADDIE model. The objectives of this research and development are (1) to produce instructional design which are syllabus, lesson plan, students whorksheet, assessment sheets, and podcast using discovery learning model and (2) to improve students‟ Scientific Skills and Cognitive Learning Outcomes trough the implementation of learning tools that have been prepared. The subjects are students of X MIPA E1 SMAN 5 Malang, East Java.  Validation test result from the validators stated that the product has average score 92,54% with very valid category. Practicality test result based on field test, conduct a pilot test, and learning syntax implementation consecutively has average score of  84,29%, 87,85%, and 100%. Effectiveness test gained from pretest, posttest, and calculation of N-gain has score 0,26 for cognitive learning outcomes and 0,069 for Scientific Skills with low Category. It can be concluded that (1) the learning tools have very valid and practical category to be implemented on biology learning, and (2) students‟ Scientific Skills and Cognitive Learning Outcomes improve after the implementation of the biology learning tools, but with low effectiveness criteria.Keywords: scientific skills, cognitive learning outcomes, discovery learning, podcast